Information-Theoretic Intrinsic Plasticity for Online Unsupervised Learning in Spiking Neural Networks - Zhang, Wenrui; Li, Peng (Frontiers in Neuroscience, 2019)
As a self-adaptive mechanism, intrinsic plasticity (IP) plays an important role in maintaining homeostasis and shaping the dynamics of neural circuits. In a computational point of view, IP has the potential in enabling promising non-Hebbian learning in artificial neural networks. While IP based learning has been attempted for spiking neuron models, the existing IP rules are ad hoc in nature and the practical success of their application has not been demonstrated particularly towards enabling real-life learning tasks. This work aims to address the theoretical and practical limitations of the existing works by proposing a new IP rule named SpiKL-IP. SpiKL-IP is developed based on a rigorous information-theoretic approach where the target of IP tuning is to maximize the entropy of the output firing rate distribution of each spiking neuron. This goal is achieved by tuning the output firing rate distribution towards a targeted optimal exponential distribution. Operated on a proposed firing-rate transfer function, SpiKL-IP adapts the intrinsic parameters of a spiking neuron while minimizing the KL-divergence from the targeted exponential distribution to the actual output firing rate distribution. SpiKL-IP can robustly operate in an online manner under complex input and network settings. Experimental studies demonstrate that the application of SpiKL-IP to individual neurons in isolation or as part of a larger spiking neural network robustly produces the desired exponential distribution. The evaluation of SpiKL-IP under real-world speech and image classification tasks shows that SpiKL-IP noticeably outperforms two existing IP rules and can significantly boost recognition accuracy by up to more than 16%.